2017
DOI: 10.1098/rsif.2016.0898
|View full text |Cite
|
Sign up to set email alerts
|

Form and function of the teleost lateral line revealed using three-dimensional imaging and computational fluid dynamics

Abstract: Fishes sense weak water motion using the lateral line. Among the thousands of described fish species, this organ may differ in size, shape and distribution of individual mechanoreceptors or lateral line canals. The reasons for this diversity remain unclear, but are very likely related to habitat preferences. To better understand the performance of the organ in natural hydrodynamic surroundings, various three-dimensional imaging datasets of the cephalic lateral line were gathered using Leuciscus idus as represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 81 publications
(140 reference statements)
1
20
0
Order By: Relevance
“…Distance downstream (cylinder diameters) Herzog et al, 2017). Moreover, flow imaging and modeling studies show that gliding fishes, which our study most closely approximates, experience the largest pressure gradient at the anterior region of the head during obstacle avoidance and wallfollowing behaviors (Windsor et al, 2010a,b).…”
Section: Hydrodynamic Signal Is Greatest At the Anterior Regionsupporting
confidence: 60%
See 1 more Smart Citation
“…Distance downstream (cylinder diameters) Herzog et al, 2017). Moreover, flow imaging and modeling studies show that gliding fishes, which our study most closely approximates, experience the largest pressure gradient at the anterior region of the head during obstacle avoidance and wallfollowing behaviors (Windsor et al, 2010a,b).…”
Section: Hydrodynamic Signal Is Greatest At the Anterior Regionsupporting
confidence: 60%
“…When fish swim, flow is induced across the head. How flow interacts with the head depends greatly on its shape and thus fish heads may receive different sensory inputs depending on their morphological variation (Chambers et al, 2014;Herzog et al, 2017). Furthermore, because the fish head is the platform upon which the lateral line lies, any differences in head shape alter the spatial position of the lateral line relative to the flow.…”
Section: Introductionmentioning
confidence: 99%
“…The functional significance of different lateral-line morphologies has also been investigated using computational fluid dynamics based on the reconstructions of three-dimensional imaging of real lateralline systems. For instance, photogrammetry and X-ray tomography of the lateral-line system of the ide Leuciscus idus (L. 1758) (Cyprinidae), showed that this fish has epidermal pits (indentations in the skin) in the anterior part of the head in addition to relatively small diameter cephalic lateral-line canals (Herzog et al, 2017). A laminar compressible flow model based on the Navier-Strokes equation revealed that both the pits and the canals reduce the stimulation of the cephalic lateral-line system by bulk water flow but do not attenuate the high frequency water motions generated by a nearby dipole source appreciably, thus increasing the ratio between high frequency local stimuli and background flow.…”
Section: The Use Of Artificial Lateral-line Systems For the Understmentioning
confidence: 99%
“…Several examples from previous studies conducted using echinoids show that in particular the possibility to rapidly inspect 3D datasets from any given perspective can trigger discoveries that would otherwise not have been possible (Ziegler 2014;Ziegler et al , 2010dZiegler et al , 2012bZiegler et al , 2016. Furthermore, studies based on digital morphology may result in data suitable for pattern recognition and shape analysis protocols (Ziegler et al 2012a, Ziegler & Menze 2013, finite element analysis (Herzog et al 2017), or a more interactive communication of complex biological structures (Ziegler et al 2011b). With regard to the letter aspect, digital morphological and anatomical data were shown to enhance academic teaching, for example through 3D interactive virtual as well as additively manufactured physical 3D models (Ziegler & Menze 2013, Kato et al 2016.…”
Section: Morphological and Anatomical Aspectsmentioning
confidence: 99%
“…Formalin-fixed, ethanol-preserved specimens were immersed in phosphotungstic acid (PTA), a staining solution containing tungsten (W). This heavy metal had previously been shown to provide good soft part contrast in different invertebrate and vertebrate taxa (Metscher 2009, Ziegler & Menze 2013, Xavier et al 2015, Herzog et al 2017, Chen et al 2018, Jahn et al 2018, Weinhardt et al 2018. The resulting datasets were qualitatively analyzed to evaluate whether a combined visualization of hard and soft parts would entail advantages for morphological and anatomical inferences in echinoderm research.…”
Section: Introductionmentioning
confidence: 99%